The Craftsman in America - Anderson .; Harney A. L.; Melhan T.; Ramsay C. R.; Raymer P. I.; Spotswood B.; Watkins C. M. (Washington, D.C. National Geographic Society, 1975)
The Craftsman in America examines the national heritage of handcrafts developed to meet basic needs of survival, conditioned by the frontier, and continued to the present. Every Americans ancestors included craftcmen; this book pays tribute to their work. Scores of examples, carefully chosen and surebly photographed, prove the craftcmans skill. You assess bowls and basckets, sikverware and tin, quilts and coverlets, elegant furnitureand weathered logs in a cabin wall.
Keywords: 745/749 . - .